Email server by using Ubuntu migrating with cloud server / Muhammad Faris Md Roslee - Md Roslee, Muhammad Faris (2014)
Dyslexia Association Malaysia which is provide learning program for Dyslexic child especially in areas of spelling, reading and calculation and was established since 1999. With having multiple branches around Malaysia Peninsular and it connected among the branches using webpages, so there is a limitation of sharing information and data among them. Thus, this project proposed to develop an email server with cloud computing architecture to help Dyslexia Association Malaysia enhance the connection between the branches. Thus, I using waterfall methodology to manage the analysis and the result from the topology that we will create during the implementation phases. It also consists of designing, developing and analyzing in the project phases. The current infrastructure of the association used a leased line with Internet connection without data canter that carry the learning materials for the instructors or teachers. This could standardize and manageable the learning materials according to learning needs for students because the resources are not sharing between branches. These may result in differences in the effectiveness of learning delivery. According through our research, the solution we use an email server with private cloud infrastructure which is suitable to solve the problem due to enhance the connection between the branches.